"Copying allowed – But be careful, errors included!" – Effects of copying correct and incorrect solutions on learning outcomes. (December 2018) - Große, Cornelia S.
Abstract: Research in the area of worked examples mostly implements a clear distinction between studying examples and solving problems. However, from a theoretical perspective, this distinction is questionable: it can be argued that it is promising to work simultaneously on worked examples and on problems, with the opportunity to refer to an example when an impasse occurs. In the present study ( N  = 139 7th grader), effects of incorrect worked examples and copying were assessed using a 2x2-factorial design (factor 1: incorrect vs. correct examples; factor 2: simultaneous vs. sequential presentation of examples and problems). The results show benefits of correct examples in learning phase and post-test. While a simultaneous presentation of examples and problems fostered learning phase scores, this result reversed in the post-test – however, a simultaneous presentation led to a lower number of unrealistic considerations in the post-test. Theoretical and practical implications are discussed. Highlights: Correct examples were beneficial for learning phase and post-test results. Presenting examples and problems simultaneously fostered learning phase results. Presenting examples and problems simultaneously reduced unrealistic considerations.